PENGARUH HEALTH EDUCATION TERHADAP SIKAP REMAJA PUTRI TENTANG SADARI DI SMAN 1 PACET KABUPATEN MOJOKERTO - Virda Yuniarti, Enny; Rohmawati, Dwi (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Breast cancer is the number two cause of death for women in Indonesia. The earlier the cancer / tumor is found then the cure rate will be higher. One of the secondary prevention of breast cancer is a breast self-exam. Lack of information on early detection efforts Ca mammary caused young women tend to be negative attitude in accepting the BSE. This study aims to proved the effect of health education on the attitudes of young women about BSE in SMA Negeri 1 Pacet Mojokerto. The research used pre-experimental design with One-Group Pre-Post Test Design. Population of all teenage girls in class XI numbered 142 to obtained a sample of 50 girls were taken by purposive sampling. Health education independent variables and the dependent variable teenage attitude about BSE. Data is take by questionnaire which use before and after health education. Before being given health education obtained a negative attitude as much as 45 adolescent girls (90%) and after being given health education obtained a positive attitude as much as 46 adolescent girls (92%). Statistical tests Mc. Nemar with use of SPSS for Windows version 20.0, the results show values of 0.000 and the value ρ α of 0.05. Because the value <then H0 is rejected, which means there is effect of health education on the attitudes of young women about BSE in SMA Negeri 1 Pacet Mojokerto. The excess in the Health Education can influence the attitudes of young women when new information regarding BSE is given with a different atmosphere from the usual lectures and demonstrations.Keywords: Attitude, BSE,Health Education